A specified numerical model of heat and mass transfer in quasi-liquid gravitation flow of the system of fuel gases purifying from carbon dioxide - A. P. Nesenchuk; V. M. Kopko; T V. Ryzhova; M. G. Pchonik (Литьë и металлургия)
А specified numerical model of heat and mass transfer in the system of quasi-liquid synthetic gases purifying from carbon dioxide is given. Numerical calculation of the heat emission coefficient according to the specified model is done. The results of the calculation are compared.